ON THE ISSUE OF CORRELATION BETWEEN SELF-REGULATION AND STATE REGULATION IN THE RUSSIAN FEDERATION - I. R. Akchurina; A. M. Tufetulov (Russian Journal of Economics and Law)
The article is devoted to the issue of legal provision of self-regulation institution. The legal model of interrelations between the state and entrepreneurship community is analyzed, the legal boundaries of self-regulation are viewed.